Differences in ground contact time explain the less efficient running economy in north african runners - Santos-Concejero, J.; Granados, C.; Irazusta, J.; Bidaurrazaga-Letona, I.; Zabala-Lili, J.; Tam, N.; Gil, S. M. (Biology of Sport, 2013)
The purpose of this study was to investigate the relationship between biomechanical variables and running economy in North African and European runners. Eight North African and 13 European male runners of the same athletic level ran 4-minute stages on a treadmill at varying set velocities. During the test, biomechanical variables such as ground contact time, swing time, stride length, stride frequency, stride angle and the different sub-phases of ground contact were recorded using an optical measurement system. Additionally, oxygen uptake was measured to calculate running economy. The European runners were more economical than the North African runners at 19.5 km · h-1, presented lower ground contact time at 18 km · h-1 and 19.5 km · h-1 and experienced later propulsion sub-phase at 10.5 km · h-1, 12 km · h-1, 15 km · h-1, 16.5 km · h-1 and 19.5 km · h-1 than the European runners (P<0.05). Running economy at 19.5 km · h-1 was negatively correlated with swing time (r=-0.53) and stride angle (r=-0.52), whereas it was positively correlated with ground contact time (r=0.53). Within the constraints of extrapolating these findings, the less efficient running economy in North African runners may imply that their outstanding performance at international athletic events appears not to be linked to running efficiency. Further, the differences in metabolic demand seem to be associated with differing biomechanical characteristics during ground contact, including longer contact times.